Motivos determinantes da eleição ou recusa de tipos de tratamentos protéticos em desdentados parciais - MARTINS, Rafael Ragonezi (2008)
The aim of the study was to explore preferences and reasons for choosing or refusing prosthetic treatments in partially edentulous patients. Clinical and oral-related quality of life measures were collected from 165 patients undergoing dental treatment in undergraduate clinical activities in the School of Dentistry of the University Federal of Goiás. Reasons for choosing or refusing prosthetic treatments were investigated using an instrument containing 32 questions about the importance of these items for the patient s decisions about treatment in a 5-point Likert scale, ranging from 1 (no importance) until 5 (absolutely important). Descriptive statistics, chi-square and ANOVA were used to compare patients preferences according to clinical independent variables. Discriminant analysis was used to analyze the impact of patients reasons for choosing or refusing removable (RPD), fixed (FD) or implant (ID) prosthesis. Results showed that older patients (p<0.001) and with greater OHIP scores (p<0,05) were more likely to choose for removable partial dentures and implant prosthesis were preferred in patients with higher school levels (p<0.01). Discriminant functions reveal that the desire of having a fixed or removable appliance had great impact on patients decisions. The removal of natural teeth structure was the main reason for refusing conventional fixed dentures and cost had great impact on refusing implant dentures. Overall agreement percentages between actual patients decisions and predicted by discriminate analysis were over 90% for all types of treatment. It was concluded that acceptance or rejection of prosthodontic modalities have great variations among patients and individual perceptions are important determinants of treatment decisions. The main reasons for choosing or refusing treatments focused in this study can be used to guide shared decision making process, providing treatments that better match patients expectations and desires